RETHINKING (DIS)FLUENCY WITHIN THE SCOPE OF INTERACTIONAL LINGUISTICS AND GESTURE STUDIES - Loulou KOSMALA (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
The study of so-called ‘disfluency’ phenomena (uh and um, filled and unfilled pauses, self-repairs and the like) has gained a lot of attention in various fields in linguistics in the past few decades, but a majority of studies tend to be production-oriented and often disregard fundamental aspects of face-to-face communication such as interactional dynamics and gesture. This paper presents a multimodal and multilevel model of “inter-fluency”, considering different levels of analysis, mainly, talk, gesture, and interaction, by combining different theoretical frameworks and methodologies in gesture studies and interactional linguistics in order to bridge this gap and go beyond previous cognitive-oriented models.